Cost-effectiveness analysis of a fecal microbiota transplant center for treating recurrent C.difficile infection. Issue 5 (November 2020) - Shaffer, Seth R; Witt, Julia; Targownik, Laura E; Kao, Dina; Lee, Christine; Smieliauskas, Fabrice; Rubin, David T; Singh, Harminder; Bernstein, Charles N
Highlights: Establishment of a fecal microbiota transplant center, when including start-up costs, is cost-effective. A minimum catchment area of 56, 849 is required when starting up a center. The cost-effectiveness reported here should be generalizable to other countries. Abstract: Objective: : We assessed the cost-effectiveness of establishing a fecal microbial transplant (FMT) unit in Canada for the treatment of recurrent CDI. Design: : We performed a cost-effectiveness analysis to determine the number of patients with recurrent CDI needed to treat (NNT) annually to make establishing a FMT unit cost-effective. We compared treating patients for their second recurrence of CDI with FMT in a jurisdiction with a FMT unit, compared to being treated with antibiotics; then sent to a medical center with FMT available for the third recurrence. We used a willingness to pay threshold of 50, 000 per quality-adjusted-life-year gained. Results: : The minimum annual NNT was 15 for FMT via colonoscopy, 17 for FMT via capsule, and 44 for FMT via enema compared with vancomycin, and 16, 18, and 47 compared with fidaxomicin, respectively. A medical center's minimum catchment area when establishing a FMT unit would have to be 56, 849 if using FMT via colonoscopy, or 64, 429 if using capsules. Conclusion: : We report the minimum number of patients requiring treatment annually with FMT to achieve cost-effectiveness, when including start-up and ongoing costs. FMT is cost-effective in Canada in populations with a sufficient number of eligible patients, ranging from 15 to 47 depending on the FMT modality used. This is crucial for medical jurisdictions making decisions about establishing a FMT unit for the treatment of recurrent CDI. The cost-effectiveness can be generalized in other countries.